We Were the Robots: Automation and Voting Behavior in Western Europe - Massimo Anelli; Italo Colantone; Piero Stanig (Institute of Labor Economics (IZA), 2019)
We investigate the impact of robot adoption on electoral outcomes in 14 Western European countries, between 1993 and 2016. We employ both official election results at the district level and individual-level voting data, combined with party ideology scores from the Manifesto Project. We measure exposure to automation both at the regional level, based on the ex-ante industry specialization of each region, and at the individual level, based on individual characteristics and pre-sample employment patterns in the region of residence. We instrument robot adoption in each country using the pace of robot adoption in other countries. Higher exposure to robot adoption is found to increase support for nationalist and radical-right parties. Unveiling some potential transmission channels, higher robot exposure at the individual level leads to poorer perceived economic conditions and well-being, lower satisfaction with the government and democracy, and a reduction in perceived political self-efficacy.
Keywords: D72; J23; J24; O33; 330; radical right; nationalism; automation